Análise dos acidentes de trabalho fatais inseridos no sistema de informação de agravos de notificação (SINAN) ocorridos em Belo Horizonte, MG - Isabela Mie Takeshita (2012)
Occupational accidents are considered preventable events and they cause great impact on the economy and society. The number of fatal accidents at work reveals a sad reality in the context of occupational health. By analyzing these accidents is possible to quantify and build indicators pointing preventive measures. The objective of this study was to analyze the characteristics of fatal occupational accidents entered into the Information System for Notifiable Diseases (SINAN) that occurred in the city of Belo Horizonte between 2008 and 2011. It was accomplished a cross-sectional epidemiological study based on secondary data obtained in SINAN of Belo Horizonte and in Mortality Information System (SIM). The variables analyzed were: year of the accident, age, sex, race, education, occupation, labor market situation, where the accident occurred, CNAE, time of the accident, hours after the beginning of the journey, the city where the accident occurred, code of CID 10 for the cause of accident, type of accident, medical care, name Unity Health Care, CID 10 diagnosis of injury and date of death. Were performed: descriptive analysis, intersections between variables and the chi-square test. Of the 151 fatalities, there was a higher frequency in males, aged 18-29 years, elementary school, mulatto, formal job contract and working in construction occupations. Fatal accidents showed an average of 37 deaths per year, most of the deaths occurred on the same day of the accident, in thoroughfare, in the morning and in the first hour of the workday. Traffic accidents were the category of cause of accident according to CID 10 most related. It was concluded that the occupations of civil construction and the causes of traffic-related accidents are noteworthy in this universe of fatal accidents at work, preventive and security measures facing these realities is needed. It is believed that this study will contribute to sensitize the responsible to report these cases, provide information to encourage the workers health surveillance and showing new paths of research in the area.